Leukocytes from Lung Transplant Recipients with Severe Primary Graft Dysfunction Adoptively Transfer Alloreactivity to Vessel Grafts Trans Vivo. (July 2018) - Knoefel, Ann-Katrin; Siemeni, Thierry; Madrahimov, Nodir; Sommer, Wiebke; Avsar, Murat; Ius, Fabio; Jansson, Katharina; Ahrens, Linda; Salman, Jawad; Kühn, Christian; Tudorache, Igor; Haverich, Axel; et al.
Abstract : Introduction: Primary graft dysfunction (PGD) is the main cause of early mortality after lung transplantation (LTx). Multiple mechanisms have been described, but the link between PGD and T cell priming and chronic rejection has not been defined. In humanized mice, we studied leukocytes from human lung recipients undergoing PGD with different kinetics and their impact on rejection of artery grafts. Methods: Segments of the pericardiophrenic arteries were procured from surplus donor lung tissue and implanted into the abdominal aorta of immunodeficient mice. Development of transplant arteriosclerosis after reconstitution with PBMC of the respective human recipient was determined at day 28. Experiments were retrospectively devided; 4 patients developing transient PGD grade ≥2 at T0. 5 patients developing PGD grade ≥2 at T24 and/or T48. Mice from groups A-C were reconstituted with PBMC from PGD+ T0 patients. Group A mice were reconstituted with PBMC from the respective allogeneic human recipient. Group B mice additionally received CD4+CD25high Treg cells with their PBMC. In Group C, administered PBMC were depleted of CD4+CD25high Treg cells. Mice from groups D-F were reconstituted with PBMC from PGD+ T24/T48 patients, with group D receiving unmodified PBMC, group E receiving Treg enriched PBMC and group F receiving PBMC depleted of Tregs. Results: Luminal occlusion of aortic vessels was higher in group D mice compared to group A. The addition of CD4+CD25high Treg cells in group B & E mice had a suppressive effect on luminal occlusion (see Figure). Conclusion: We conclude that leukocytes from lung transplantation recipients undergoing PGD 2 or 3 transfer enhanced alloreactivity to humanized mice already immediately perioperatively. Therein, PGD 2 or 3 at T24 and/or T48 hours after lung transplantation translates to more severe rejection in humanized mice than transient PGD 2 or 3 at T0 only. This inflammatory response is suppressed by CD4+CD25high Treg cells indicating a potential target for future interventions in lung transplantation. Figure. No caption available.